Towards Social Protection 4.0 : An Assessment of Thailand’s Social Protection and Labor Market Systems - World Bank (World Bank, Bangkok, 2021)
This paper reviews Thailand’s social protection (SP) and labor market systems, to assess how they can be strengthened to address the key trends that will shape its society and economy in the coming decades. Thailand’s aging population, persistent high levels of workforce informality and the changing nature of work are already putting pressure on the current system, leaving most workers without protection from shocks or the ability to smooth consumption over their life cycle. For most of the growing elderly population, the small Old Age Allowance is the only form of income support. Although Thailand has made remarkable progress on poverty reduction in the past two decades, the poverty rate ticked up in 2016 and again in 2018, due to a slowing economy, droughts and wage stagnation, and the economic impacts of COVID-19 will further erode hard-won poverty gains. Adapting to changing skill needs and increasing automation requires lifelong education and training to meet rapidly evolving labor demands.